Size of Offer, Over-subscription Ratio and Performance of Malaysian IPOs (Malaysian Management Journal, 2002)
This paper examines the initial and the long-run performance of initial public offerings (IP0s) stocks listed on the Main Board of the Kuala Lumpur Stock Exchange. This study finds a significant mean initial return and mean over-subscription ratio, even-though not as high as reported in earlier studies. Size of offer is not correlated with the over-subscription ratio. In general, initial returns. are significantly higher than returns for subsequent longer-term holding periods. Mean initial returns among the three types of issue compared are not significantly different from each other Only in the case of offer for sale that we find a significant positive correlation between its over-subscription ratio and its initial return. Offer for sale also shows a positive correlation between its over-subscription ratio and its raw let11111 far day-365, but turns significantly negative for day-910 and day-] 095. In the case of combination of public issue and offer for sale, over-subscription ratio is not significantly correlated with longer- term returns, for either raw or adjusted return. Finally, in the case of public issue, its over-subscription ratio is significantly correlated with its raw return only for day-180 and day-540, and for its adjusted return, the correlation is significant only for day-180 and day-365.